Risiko Terjadinya Adiksi Internet pada Remaja dengan Gangguan Pemusatan Perhatian dan Hiperaktivitas: Sebuah Laporan Kasus Berbasis Bukti - Dewanto Andoko; Darien Alfa Cipta; Tirta Darmawan Susanto (CV. Jasa Sukses Abadi, 2023)
Attention Deficit Hyperactivity Disorder (ADHD) constitutes a prominent neurodevelopmental disorder frequently observed in childhood, characterized by three core symptoms encompassing inattention, hyperactivity, and impulsivity. Notably, the persistence of ADHD can extend from childhood into adolescence and even adulthood. Importantly, it has been noted that in nearly half of cases where ADHD endures beyond childhood and into the later stages of life, there is a substantial elevation in the risk of various addictive behaviors, encompassing alcohol, nicotine, other substances, and behavioral addictions like internet addiction, in comparison to individuals without a history of ADHD. Against this backdrop, the present literature exploration is specifically focused on discerning the influence of childhood ADHD on the propensity for internet addiction in adolescence and young adulthood. To comprehensively address this query, a meticulously structured search was conducted across several renowned databases including Pubmed, EBSCOhost, Scopus, and ProQuest. The search parameters were thoughtfully adapted and refined to align seamlessly with the clinical question, ensuring the retrieval of pertinent and valuable information. Among the amassed results, one article was identified as particularly pertinent, serving as a concise compilation of the most recent insights into the intricate interplay between ADHD and internet addiction. The outcomes derived from this thorough meta-analytical review not only establish a substantial association between childhood and adolescent ADHD and an augmented susceptibility to internet addiction in later years but also provide quantification through a notable Crude Odds Ratio (COR) of 3.76 (95% CI: 2.75, 5.15) and an Adjusted Odds Ratio (AOR) of 2.51 (95% CI: 2.09, 3.02) following meticulous confounder adjustments. Furthermore, a striking observation emerges wherein adolescents grappling with internet addiction manifest intensified ADHD symptoms, corroborated by evident elevation in Abbreviated Conners Rating Scale scores relative to their non-addicted counterparts. Collectively, these findings underscore the imperative of recognizing and addressing the heightened risk of internet addiction among adolescents with a history of ADHD and spotlight the pressing need for nuanced interventions and comprehensive support strategies.